Biochemistry & Molecular Biology of Plants - Buchanan, Bob B;Ed. Gruissem, Wilhelm;Ed (Wiley Blackwell, 2015)
* A major new edition of this highly successful, authoritative, superbly illustrated text * Distinguished, internationally renowned Editors * Completely revised with over half of the chapters having a major rewrite * Includes two new chapters on signal transduction and responses to pathogens